2015
DOI: 10.1007/s11695-015-1676-9
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Malnutrition, Trace Metal, and Vitamin Deficiency Post Roux-en-Y Gastric Bypass—a Prospective Study of 20 Patients with BMI <35 kg/m2

Abstract: This is the first prospective cohort to investigate malnutrition after RYGB in nonseverely obese patients. These patients are at risk of developing iron, selenium, and zinc deficiencies within 24 months, as well as osteopenia despite an increase in bone formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 40 publications
(51 reference statements)
0
15
0
Order By: Relevance
“…10 While studies have shown that nutritional deficiencies are usually prevalent beforehand in obese patients, bariatric surgery may exacerbate the problem and/or introduce new deficiencies. 15,23,24 According to a biochemical assessment of various nutritional parameters, approximately half of the patients in the current study were deficient in iron, haemoglobin and MCV, all of which are indicators of anaemia. A recent review article reported iron deficiency to be the most common nutritional deficiency following bariatric surgery.…”
Section: Discussionmentioning
confidence: 85%
“…10 While studies have shown that nutritional deficiencies are usually prevalent beforehand in obese patients, bariatric surgery may exacerbate the problem and/or introduce new deficiencies. 15,23,24 According to a biochemical assessment of various nutritional parameters, approximately half of the patients in the current study were deficient in iron, haemoglobin and MCV, all of which are indicators of anaemia. A recent review article reported iron deficiency to be the most common nutritional deficiency following bariatric surgery.…”
Section: Discussionmentioning
confidence: 85%
“…Bariatric surgery is known to be extremely safe, with low peri-operative mortality and complication rates [ 55 57 ]. Although other long-term potential complications of bariatric surgery exist (including gastroesophageal reflux [ 58 ], internal herniation [ 59 ], and trace element malnutrition [ 60 ]), these issues are relatively uncommon in modern bariatric surgical practice, and management strategies are available to treat these conditions should they occur. Finally, from the perspective of statistical analysis, the Egger test was utilised to measure for the presence of potential bias.…”
Section: Discussionmentioning
confidence: 99%
“…Although common micronutrient and macronutrient deficiencies (e.g. protein, iron, vitamins A, B12, C, D) in patients after gastric bypass are widely reported in the nutritional and gastroenterological literature [13], there are limited data on the prevalence, timing, and symptoms of zinc deficiency (as well as pyridoxine, selenium, and fatty acid deficiencies) after gastric bypass [1,14].…”
Section: Discussionmentioning
confidence: 99%